O estágio supervisionado: experiências vividas e a aquisição de competências para uma ação pedagógica transformadora - GONÇALO, Dulcilene Pereira do Couto (2020)
The circulation of scientific knowledge acts in the construction of a culture of knowledge and feeds it recurrently, so that it makes it pass through the historical space-time where the concrete experience was lived, carries forward what was looked at, heard and written, leads to so many pairs and instances that can not be measured. This communication of the lived, and shared of the learned, is the inspiration that served as fuel for this Report of Experience to be produced, and proposed as Work of Completion of the Course of Pedagogy of the UFPA, campus Bethlehem. The situations targeted in the present report and taken to the reflective analysis, were extracted from the experiences observed in the supervised stage in elementary education, carried out in a public school unit, namely, Casa Inês Santa Inês School. This school was the stage of the educational interventions that had the objective of collaborating with the development of the mathematical learning of the children of the 3rd year of elementary school. However, the purpose of this Report of Experience goes beyond the simple narrative of this intervention, has the function of putting in focus elements that have stood out to the investigative action of the observer and are here problematized, in the occasion to raise discussions about the value of the dialogical relation between the theory and practice in the pedagogical practice of the teacher, as well as the considerations about the Practice of Reflection and its strength in the formation of the teaching identity, promoting a critical posture of this professional of education that considers the concrete subjects of the educational act, and thus acquired competences for a transforming pedagogical action.